Amino pyridine derivatives as new corrosion inhibitors for protection cabling metal of crude oil well during acidizing - Madiha M. Hegazy; Eid M. Khalil; Emad Badr; Mahmoud A.F. Mansour (Egyptian Journal of Petroleum)
Acidizing, which is essential in crude oil wells, improves oil/gas flow by injecting acid chemicals. HCl is frequently used to increase production. Add inhibitor chemicals to reduce acid stimulation and metal corrosion. Oil and gas well corrosion is successfully inhibited by amphiphilic amino pyridine derivatives. In this study, three cationic amphiphilic amino pyridine derivative inhibitors were synthesized and evaluated by FT-IR and 1H NMR analysis. These inhibitors exhibit cost-effective, eco-friendly, and highly effective inhibition reactivity for corrosion prevention. The surface activity was evaluated at 250,400 and 60 °C in 1 mol HCl, where CMC values increase and surface tension decreases as temperature increases. The corrosion inhibition efficacy (%ηw) was determined using gravimetric methods at various temperatures of 250,550, and 70 °C which revealed that SAHBR has a higher efficacy (94.5% at 25 °C, 92.3% at 55 °C and 91.1% at 70 °C) than SADBR (92.9% at 25 °C, 90.5% at 55 °C and 88.4% at 70 °C) and SAOBR (91.6% at 25 °C, 89.7% at 55 °C and 87.0% at 70 °C) for 400 ppm dose. Also, the inhibition efficacy (%ηp) which determined through potentiodynamic polarization technique which display SAHBR is 95.90% higher than SADBR is 93.90% and SAOBR is 89.90% at 25 °C for 400 ppm dose and electrochemical impedance spectroscopy (EIS) practice which parade the inhibition efficacy (%ηE) of the synthesized inhibitors where SAHBR is 91.7% higher than SADBR is 89.0% and SAOBR is 87.3% at 25 °C for 400 ppm dose. Density Functional Theory (DFT) computed quantum chemistry parameters using B3LYP level, 6-311G+ (d, p) basis sets. Calculations included EHOMO, ELUMO energies, energy gap (ΔE), softness (σ), chemical hardness (η), electrophilicity (ω), electronegativity (X), and electron transfer (ΔN) to validate amphiphilic inhibitors' inhibition properties. Molecular Dynamics Simulation (MDS) ensured system equilibrium.